National Youth Survey (United States): Wave V, 1980 - Elliott, Delbert S. ([Verlag nicht ermittelbar], 1989)
Youth data for the fifth wave of the National Youth Survey are contained in this collection. The first wave of this survey was conducted in 1976 (ICPSR 8375), the second wave in 1977 (ICPSR 8424), the third wave in 1978 (ICPSR 8506), and the fourth wave in 1979 (ICPSR 8917). For this wave, youths in the United States were interviewed in early 1981 about events and behavior occurring in calendar year 1980. Data are available on the demographic and socioeconomic status of respondents, disruptive events in the home, neighborhood problems, youth aspirations and current successes, normlessness, labeling by parents, friends, and co-workers, perceived disapproval, attitudes toward deviance, exposure and commitment to delinquent peers, sex roles, interpersonal violence, attitudes toward sexual violence, pressure for substance abuse by peers, drug and alcohol use, and victimization.